1994
DOI: 10.1172/jci117031
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-10 in T helper cell dysfunction in asymptomatic individuals infected with the human immunodeficiency virus.

Abstract: The loss of T helper cell (TH) function in asymptomatic HIV type 1-infected individuals occurs before the decline in CD4+ T cells. At least part of the loss in TH function results from changes in immunoregulatory cytokine profiles. To investigate the role of IL-10 in such dysregulation, we tested whether: (a) expression of IL-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
210
3
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(233 citation statements)
references
References 43 publications
(13 reference statements)
13
210
3
3
Order By: Relevance
“…IL-10 can be produced by different cell types, which may explain the conflicting data on IL-10 production in HIV-1 infection reported so far. In line with other monokines, the increase in IL-10 production in HIV-l-infected individuals [10,36,41,51,60] might be due to production by mainly monocytes [45]. Unresponsiveness of T cells might be the cause of the observation that IL-10 production is decreased or unaltered in other studies [28,42,48,99,166].…”
Section: 153]supporting
confidence: 60%
See 1 more Smart Citation
“…IL-10 can be produced by different cell types, which may explain the conflicting data on IL-10 production in HIV-1 infection reported so far. In line with other monokines, the increase in IL-10 production in HIV-l-infected individuals [10,36,41,51,60] might be due to production by mainly monocytes [45]. Unresponsiveness of T cells might be the cause of the observation that IL-10 production is decreased or unaltered in other studies [28,42,48,99,166].…”
Section: 153]supporting
confidence: 60%
“…Indeed, addition of neutralizing antibodies to T cell cultures enhances proliferative responses [36,166]. In the original studies by Clerici et al [33], neutralizing anti-IL-4 mAb were shown to be capable of restoring proliferative responses, but seemed to be much less efficient than anti-IL-10 antibodies [36].…”
Section: Cytokines and Immune Modulationmentioning
confidence: 99%
“…IL-10 has been associated with the induction of parasite antigen-specific T cell anergy in asymptomatic microfilaremic filariasis patients (King et al 1993), schistosomiasis (King et al 1996), leishmaniasis (Ghalib et al 1993) and toxoplasmosis (Candolfi et al 1995). Suppressed costimulatory signalling has also been proposed as the cause of anergy of T H 1 cells that leads to apoptosis during HIV infection (Clerici et al 1994) and leprosy (Sieling et al 1993).…”
Section: T Cell and Monocyte/macrophage Re-sponsesmentioning
confidence: 99%
“…IL-10 producing HIV-specific CD4 ϩ regulatory T cells suppressed both CD4 ϩ and CD8 ϩ HIV-specific T cell function in vitro (14 -16). Previous studies have found that the proliferation of CD4 ϩ T cells from HIV-infected individuals was inversely associated with the levels of IL-10 and that responses were partially restored by anti-IL-10 Abs (17,18). In addition, a higher frequency of CD4 ϩ T cells producing IL-10 was associated with a more progressive HIV disease (19).…”
mentioning
confidence: 98%